Iodixanol Nasal Solution Reduces Allergic Rhinoconjunctivitis Signs and Symptoms in Allergen BioCube®: Randomized Clinical Trial - Gomes PJ; Abelson MB; Stein L; Viirre E; Villafranca JE; Lasser EC (Global Journal of Allergy - Peertechz Publications, 2018)
Importance: Allergic rhinitis affects about 20% of the population worldwide. Available pharmacological treatments are helpful but not ideal in providing relief; safer and more effective treatments are needed. Objective: To evaluate the efficacy and safety of Nasapaque nasal solution vs placebo for relief or prophylactic treatment of seasonal allergic rhinitis. Design: Single-center, double-masked, RCT (March to July 2015) conducted outside of ragweed season.  Setting: Study conducted in the Allergen BioCube®. Participants: Adult subjects (aged ≥ 18 years) with history of allergic rhinitis, positive skin test for ragweed, and positive BioCube challenge response.  Interventions: Day 1: Subjects received treatment (250 µl/nostril) followed by 7.5-hr BioCube ragweed exposure. Day 8: Subjects received treatment prior to 3.5-hr BioCube ragweed exposure.  Main Outcomes and Measures: Primary endpoint: Total Nasal Symptom Score (TNSS, 0-12 scale), comprised of four individual nasal symptom scores. Secondary endpoints: Peak Nasal Inspiratory Flow (PNIF) and nasal inflammation score. Exploratory endpoints: Total Ocular Symptom Score, comprised of three ocular symptom scores. Safety was evaluated at all visits. P<0.10 was statistically significant in this proof-of-concept study; p<0.05 is also reported.  Results: Of 73 enrolled subjects, 67 completed the study. Nasapaque onset of action for TNSS was 15 min (change from baseline [CFB]: Nasapaque = -3.2±2.50, placebo = -2.3±2.33, 80% CI -1.6 to -0.2, p = 0.060); efficacy occurred as late as 4 hr 15 min (CFB: Nasapaque = -4.1±2.90, placebo = -3.1±2.51, 80% CI -1.7 to -0.1, p = 0.075). Results were notable for nasal itching (4 hr 30 min CFB: Nasapaque = -1.2±0.95, placebo = -0.8±0.84, 80% CI -0.7 to -0.1, p = 0.044) and ocular itching (CFB: 25 min: Nasapaque = -1.0±0.86, placebo = -0.4±0.94, 80% CI -0.8 to -0.3, p = 0.006). Nasapaque scores were also statistically significant for PNIF and nasal inflammation. Allergen exposure in the BioCube induced nasal and ocular allergy responses in subjects. Conclusions and Relevance: Nasapaque was effective and safe in providing relief of nasal and ocular AR symptoms. Clinical trials with models such as the Allergen BioCube provide valuable assessments of allergen exposures and drug efficacies. Further studies with Nasapaque are warranted.  Trial Registration clinicaltrials.gov Identifier: NCT02377895